2022
DOI: 10.3390/biom12111636
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Its Analogs in Non-Small Cell Lung Cancer Treatment: Challenges and Expectations

Abstract: Researchers have made crucial advances in understanding the pathogenesis and therapeutics of non-small cell lung cancer (NSCLC), improving our understanding of lung tumor biology and progression. Although the survival of NSCLC patients has improved due to chemoradiotherapy, targeted therapy, and immunotherapy, overall NSCLC recovery and survival rates remain low. Thus, there is an urgent need for the continued development of novel NSCLC drugs or combination therapies with less toxicity. Although the anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 186 publications
0
12
0
Order By: Relevance
“…Also, in examining the expression of the P53 gene as a tumor suppressor gene, the effect of curcumin alone has shown an increase in expression in A549 cells. Tang et al [27] also noted in a review study the effect of curcumin on non-small cell lung cancer cells, increasing the expression of the P53 gene.…”
Section: Discussionmentioning
confidence: 91%
“…Also, in examining the expression of the P53 gene as a tumor suppressor gene, the effect of curcumin alone has shown an increase in expression in A549 cells. Tang et al [27] also noted in a review study the effect of curcumin on non-small cell lung cancer cells, increasing the expression of the P53 gene.…”
Section: Discussionmentioning
confidence: 91%
“…Natural therapeutic products can offer similar effects with a much more tolerable therapeutic index 41 . We selected CAPE, curcumin, and DATS specifically to be used in this study as they exhibit some of those properties and also been employed as potential mono‐therapeutic agents against lung cancer 42–44 . Among these three natural compounds, CAPE showed the most promise as the natural therapeutic agent which could be utilized in combination with AZD9291 to overcome EGFR‐TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…41 We selected CAPE, curcumin, and DATS specifically to be used in this study as they exhibit some of those properties and also been employed as potential mono-therapeutic agents against lung cancer. [42][43][44] Among these three natural compounds, CAPE showed the most promise as the natural therapeutic agent which could be utilized in combination with AZD9291 to overcome EGFR-TKI resistance. We found that CAPE synergistically enhanced the AZD9291-induced cytotoxic effects as it significantly decreased the IC 50 of AZD9291.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of NSCLC is directly related to the cancer stage (Mithoowani & Febbraro, 2022). As medical technology advances, effective methods of treating NSCLC are constantly being introduced, but the 5‐year survival rate remains low (Duma et al., 2019; Tang et al., 2022). The mortality of NSCLC in China is still higher than in Western countries (Chen et al., 2022).…”
Section: Introductionmentioning
confidence: 99%